Description of Work Fatigue on Nurses at Naimata Mental Hospital Kupang - Indrasari, Yuningsi; Setyobudi, Agus; Doke, Soni; Junias, Marylin (Timorese Journal of Public Health, 2021)
Work fatigue in nurses is one of the problems in human resource management in hospitals. Naimata Mental Hospital Kupang is a hospital that specifically treats patients with psychosocial disabilities or people with mental disorders, as well as being the first mental hospital in East Nusa Tenggara (NTT) which is the main reference for people with mental disorders. Naimata Mental Hospital Kupang has 42 nurses with 47 patients who require maximum 24-hour supervision by expert doctors and competent nursing staff. This study aims to describe work fatigue in nurses at the Naimata Mental Hospital Kupang. The type of research is descriptive research which is studied quantitatively. The study was conducted at the Naimata Mental Hospital Kupang in July 2021. The total population and sample in this study amounted to 42 nurses at the Naimata Mental Hospital Kupang. The technique of collecting work fatigue data uses a questionnaire to measure feelings of work fatigue (IFRC). The results showed that from 42 respondents, at most 25 people (59.5%) experienced work fatigue in the light category and 17 people (40.5%) experienced work fatigue in the severe category. It is recommended for nurses to stretch the muscles on the sidelines of work or while resting.